Corporate social responsibility disclosure in Malaysian government-linked companies - Elinda Binti Esa (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2011)
This study mainly investigates corporate social responsibility (CSR) disclosure in the annual reports of Malaysian government – linked companies (GLCs). Although a number of studies have looked into CSR in Malaysian companies, very little or limited research has been done on GLCs. CSR can be defined as a subject that covers from business ethics, good governance and legal practices to social obligation and sustainable environment. Being a business where the government has a major ownership and control, GLCs can be expected to lead others in good governance practices including CSR practice. That is because the objective of GLCs' formation is not purely profit driven but includes social aspects to ensure a more equitable society. This study examines the CSR items most disclosed, the extent of CSR disclosure and to examine whether corporate characteristics and corporate governance characteristics are good explanatory variables in determining CSR disclosure among 27 GLCs for the years 2005 and 2007. The two years were chosen to see if the introduction of the Silver Book in 2006 has an impact on CSR disclosure. A CSR disclosure checklist was used to score the items in the annual reports. The t test and non-parametric Mann- Whitney test showed that the extent of disclosure was higher in 2007 and the difference was statistically significant at the 5% level. This result appears to suggest that the introduction of the Silver Book in 2006 has had positive impact on CSR in Malaysian GLCs. The results further revealed that board size was a significant variable influencing CSR disclosure in 2005. It would appear that larger board size would stimulate healthier discussions on CSR and hence involvement and disclosure of those activities in corporate annual reports.